Regulators and the Poor : Lessons from the United Kingdom - Green, Richard (The World Bank, 1999)
July 2000 - The United Kingdom generally fights poverty directly-through the government's benefit system-and not through utilities. But British regulators have taken certain measures that help utility consumers (mostly, but not always, poor consumers). Other countries may be able to copy some of their techniques. Green studies a number of ways in which British regulators have helped poorer consumers. British Telecommunications offers a lower user tariff and a very cheap service with most outgoing calls barred, to attract customers who could not afford the full service. The gas regulator has taken action to reduce price differentials between customers who pay in cash (mostly, but not always, poor customers) and those who pay with bank transfers (mostly, but not always, better off customers). The electricity industry faces a series of rules and codes of practice governing its dealings with domestic consumers. Some of these schemes will help all consumers; others are aimed at, but not exclusive to, the poor. One challenge facing utilities in some countries is that of expanding their networks to reach millions of unserved (mostly poor) customers. The United Kingdom achieved nearly universal service in geographical terms while the utilities were state-owned. The utilities were serving some customers who were already profitable and were simply required to serve others, who might not be. It might be possible to grant a concession, or privatize a new company, on a similar basis of bundling social obligations with opportunities for profit, but it will be important to ensure that obligations are performed properly. U.K. regulators have been fairly successful at protecting existing customers; other countries may be able to copy some of their techniques.